2000
DOI: 10.4133/jeeg5.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Shear-Wave Velocity Profiles from MASW with Borehole Measurements in Unconsolidated Sediments, Fraser River Delta, B.C., Canada

Abstract: Recent field tests illustrate the accuracy and consistency of estimating near-surface shear (S) wave velocities calculated using Multi-channel Analysis of Surface Wave (MASW). To evaluate the technique in a variety of near-surface conditions and through a wide range of velocities, MASW-derived S-wave velocity profiles (S-wave velocity vs. depth) were statistically compared to S-wave velocity profiles measured in seven boreholes in the unconsolidated sediments of the Fraser River delta, near Vancouver, B.C., Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 139 publications
(54 citation statements)
references
References 11 publications
0
54
0
Order By: Relevance
“…By using an array of receivers, multimodal dispersion curves from a MASW survey are presented in the form of energy bands to form a dispersion spectral image. XIA et al (2000a) demonstrated that the fundamental-mode phase velocities obtained through a MASW study generally provide reliable estimates of the shear-wave velocities (Vs). The method has been employed in various applications in engineering geology (e.g., MILLER et al, 1999a,b;PARK et al, 1998PARK et al, , 1999bPARK et al, , 2000XIA et al, 1998XIA et al, , 1999XIA et al, , 2000a.…”
Section: Introductionmentioning
confidence: 99%
“…By using an array of receivers, multimodal dispersion curves from a MASW survey are presented in the form of energy bands to form a dispersion spectral image. XIA et al (2000a) demonstrated that the fundamental-mode phase velocities obtained through a MASW study generally provide reliable estimates of the shear-wave velocities (Vs). The method has been employed in various applications in engineering geology (e.g., MILLER et al, 1999a,b;PARK et al, 1998PARK et al, , 1999bPARK et al, , 2000XIA et al, 1998XIA et al, , 1999XIA et al, , 2000a.…”
Section: Introductionmentioning
confidence: 99%
“…The results are represented in the form of average relative differences in all layers of soil. The average relative difference describes the overall differences between shearwave velocities from the MASW method and the empirical borehole method (Xia et al, 2000). These results are shown in Table 3.…”
Section: Masw Bh2mentioning
confidence: 64%
“…Based on their experience, the fundamental-mode phase velocities, when calculated with high accuracy (e.g., Xia et al, 2000b), can generally provide reliable S-wave velocities (±15%). The accuracy can be increased if higher modes of surface waves are available and included in the inversion process (Xia et al, 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy can be increased if higher modes of surface waves are available and included in the inversion process (Xia et al, 2000a). Recent advances in the use of surface waves for near-surface imaging incorporated Multichannel Analysis of Surface Waves (MASW) (Park et al, 1996(Park et al, , 1999a(Park et al, , and 1999bXia et al, 1997Xia et al, , 1999Xia et al, , and 2000b) with a standard common depth point (CDP) roll-along acquisition format (Mayne, 1962) similar to conventional petroleum exploration data acquisition. Combining these two uniquely different approaches to acoustic imaging of the subsurface allows high confidence, non-invasive delineation of horizontal and vertical variations in near-surface material properties , Xia et al, 2000c.…”
Section: Introductionmentioning
confidence: 99%